CLINICAL EVALUATION OF CHILDREN WITH NEUROCIRCULATORY DYSTONIA - Umarova Mukaddas Abdukadirovna (Scholar Express Journals, 2024)
The purpose of the article is to study the clinical features of children with neurocirculatory dystonia (NCD) of the hypertensive type. The study included 30 children aged 7 to 16 years with hypertensive type NCD, who were examined and treated in the cardiology department of the Andijan Regional Children's Clinical Hospital.
Keywords: children; neurocirculatory; dystonia of the hypertensive type